Preparation of chiral EC(sp3)E’ phosphine-based mono- and di-nuclear palladium pincer complexes - Tay, Wee Shan (2016)
Ten enantiopure Pd pincer complexes with aliphatic and unsymmetrical characteristics have been synthesized efficiently. Chirality on the ligand backbone was introduced via an asymmetric H-P bond addition reaction by two structurally-dissimilar catalysts with >99% ee’s. Challenging C(sp3)-H bond activation during palladation proceeded with high yields and excellent diastereoselectivities under optimized conditions. Several crystal structures were isolated and discussed. Selected pincer complexes were also employed in a chirality “self-breeding” protocol, in which infinite replicates of a catalyst may be synthesized by itself. Excellent results were obtained, with the selected complex being capable of producing itself with the exact absolute stereoconfiguration with >99% ee at RT.